Investigation on the Effect of Different Mild Acidic Electrolyte on ZIBs Electrode/Electrolyte Interface and the Performance Improvements With the Optimized Cathode - Gui, Yang; Lei, Yang; Fan, Bao An (Frontiers in Chemistry, 2020)
Zinc ion batteries (ZIBs), as an promising alternatives of lithium ion batteries (LIBs), have aroused revived interest in the energy storage field recently. To obtain good performance, the choice of electrolyte plays a vital role. Therefore, in this data report, three kinds of inorganic aqueous electrolyte has been assessed for interfacial effect and ZIB performance. Through the comparison, ZnSO4 electrolyte shows advantages on ionic conductivity over both Zn(NO3)2 and Zn(CH3COO)2 solution, Zn(CH3COO)2 exhibits considerable Zn stripping/plating kinetics with ZnSO4, and there is no characteristic peak pair of Zn dissolution/deposition found in Zn(NO3)2.Additionally, a lower charge transfer resistance was proved when the cell with 1 M ZnSO4 solution. Furthermore, cells with activated graphite paper in ZnSO4 solution has been investigated as well. The results suggests an enhanced cell performance which is attributed to the increased specific surface area of the graphite paper after the activation.